Avaliação da atividade antibacteriana da paroxetina frente Staphylococcus aureus: estudo na forma planctônica, em biofilme e potencial aplicação em cateter - Cabral, Vitória Pessoa de Farias (2023)
Staphylococcus aureus is characterized as a human pathogen associated with high rates of infection, which since the 1960s has presented methicillin-resistant isolates that emerged, spread globally and become one of the main causes of bacterial infections in healthcare environments and community. In this sense, the repositioning of drugs constitutes a therapeutic possibility. Paroxetine, a selective serotonin reuptake inhibitor, is the subject of research in this area. Thus, the objective of the study was to evaluate the in vitro antibacterial activity of paroxetine against strains of S. aureus sensitive and resistant to methicillin in planktonic form and its action on biofilm formed and in formation. To determine the Minimum Inhibitory Concentrations (MIC), the broth microdilution technique was used according to the CLSI M07-A10 protocol (2015), and the Minimum Bactericidal Concentration (MBC) and tolerance level of paroxetine were subsequently established. In addition, the checkerboard was used to evaluate the pharmacological interaction between paroxetine and oxacillin, followed by the use of Scanning Electron Microscopy (SEM) in planktonic cells. Regarding the investigation of possible mechanisms of action, flow cytometry, fluorescence microscopy and molecular docking tests were carried out. With regard to assays in sessile cells, the action of drugs was evaluated against biofilm formed and in formation using 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-bromide tetrazolium (MTT), and in the prevention of biofilm formation in peripheral venous catheters by counting Colony Forming Units (CFU/mL) and SEM. Paroxetine showed MIC of 64 µg/mL, bactericidal activity and mostly additive interactions in combination with oxacillin. Evidence of action on genetic material and membrane was also found, in addition to morphological changes in the microbial cell and activity on virulence factors. Paroxetine exhibited a significant reduction in cell viability from 32 µg/mL in the formed biofilm and 128 µg/mL in the biofilm in formation and, in combination with oxacillin, significance was verified from the associated MICs. Paroxetine alone and associated with oxacillin showed potential for preventing the formation of S. aureus biofilm in peripheral venous catheters with a reduction of 44.81% and 94.94% in CFU/mL, respectively. Therefore, paroxetine demonstrates promising activity against S. aureus, characterizing itself as a possible therapeutic alternative.